Vila Tomšičeva: Prostorsko-arhitekturne rešitve - Sitar, Metka; Šprah, Nataša (2019)
Villa Tomšičeva: Special-architectural solutionsThe appearance of the abandoned villa on Tomšičeva Street 13 degrades one of the most beautiful urban are as of individual, predominantly residential buildings with characteristic urban design parallel to the protected chestnut alley. The student development project at the Faculty of Civil Engineering, Traffic Engineering and Architecture, University of Maribor, initiated by the owner of the property - the company Invenio, Maribor -, discusses the problematic of the reconstruction of the existing building and the possibilities of new construction on the plot. The introduction outlines the history of the building and its surroundings as a precondition for diverse approaches to functional and architectural redesign of the villa, as well as urban and architectural design of new objects with complementary contents on the plot. In continuation, we describe the process of student work by representing nine student project solutions harmonized in cooperation with the representatives of property owner. The results summarize the description and presentation of various design solutions of the reconstruction of the villa, as well as the incorporation of additional buildings in the area of this attractive location.
Keywords: villa; reconstruction; student project; Tomšičeva Street; Maribor